2018
DOI: 10.3390/g9040091
|View full text |Cite
|
Sign up to set email alerts
|

From Social Information to Social Norms: Evidence from Two Experiments on Donation Behaviour

Abstract: While preferences for conformity are commonly seen as an important driver of pro-social behaviour, only a small set of previous studies has explicitly tested the behavioural mechanisms underlying this proposition. In this paper, we report on two interconnected experimental studies that jointly provide a more thorough and robust understanding of a causal mechanism that links social information (i.e., information about the generosity of others) to donations via changing the perception of a descriptive social nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 56 publications
2
38
0
1
Order By: Relevance
“…If it would function as a reference point, then any number would influence donation behavior by simply working as an unconscious suggestion (i.e., a nudge; Thaler & Sunstein, 2008). Goeschl et al (2018) found that providing donors with a random number, instead of a number based on a donation amount of a previous donor, did not influence the donation behavior. Van Teunenbroek & Bekkers (2018) argue against the possibility that social information functions as a reference point, because donors in their field experiment did not exactly donate the suggestion amount of 82.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…If it would function as a reference point, then any number would influence donation behavior by simply working as an unconscious suggestion (i.e., a nudge; Thaler & Sunstein, 2008). Goeschl et al (2018) found that providing donors with a random number, instead of a number based on a donation amount of a previous donor, did not influence the donation behavior. Van Teunenbroek & Bekkers (2018) argue against the possibility that social information functions as a reference point, because donors in their field experiment did not exactly donate the suggestion amount of 82.…”
Section: Discussionmentioning
confidence: 92%
“…People tend to value prior information and use this information as a reference point for behavioral adjustments, which is also known as anchoring (Hammond, Keeney, & Raiffa, 1998). Goeschl et al (2018) examined whether social information functions as a mere reference. If it would function as a reference point, then any number would influence donation behavior by simply working as an unconscious suggestion (i.e., a nudge; Thaler & Sunstein, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations